The armageddon code - Lee, Stan, 1922-2018; Bonansinga, Jay R. (Lee, Stan, 1922-2018. Stan Lee's The devil's quintet., 2022)
"A five-person special ops unit, composed of a diverse assortment of former Navy SEALS from all walks of life, are responding to a terrorist threat deep in the Caucasus Mountains when their mission goes south in a big way. Facing certain death and torture, they're unexpectedly offered a Faustian bargain by the Devil himself, who grants them unearthly powers in order to send evildoers to Hell on his fiendish behalf. But "The Devil's Quintet" do things their own way, fighting to protect America and the world, while trying their best not to let their hellish new abilities corrupt them beyond redemption."--